Pengaruh Pembelajaran Kontekstual Terhadap Hasil Belajar Siswa pada Mata Pelajaran IPA Kelas VI SD Kuwu Ruma Desa Lambu Kecamatan Lambu Kabupaten Bima. - ilham, ilham -; Siska Dwi Astiati, Siska Dwi Astiati - (Jurnal Ilmiah Mandala Education (JIME), 2023)
This study aims to determine the effect of a contextual approach to science learning outcomes for sixth grade students at SDN Kuwu Ruma. This type of research is an experiment with a quantitative approach. This study used two groups: the experimental group and the control group. The experimental group is the group that was given the science learning treatment with a contextual approach. The control group is the group that was given the science learning treatment with a conventional approach. The research sample for class VI students at SDN Kuwu Ruma was 30 students. Sampling used a cluster random sampling technique with a posttest only control design. Data collection used multiple choice test instruments, then the normality of the data was calculated using Lilliefors and the homogeneity of the data using Fisher. The results of the normality and homogeneity tests show that the data are normally distributed and the two data have homogeneous variants. Then analyzed using t-test. Based on the calculation of the t-test, the value of tcount = 3.50 and ttable = 1.69 and a significant level of 0.05 so that Hi is accepted and Ho is rejected. The results showed that the contextual approach had a significant effect on the science learning outcomes of sixth grade students at SD Kuwu Ruma, Lambu Village, Lambu District. These results indicate that the contextual approach can be used as an alternative in developing science learning outcomes for sixth grade elementary school students.